Assessing the Lead Removal Potential of Pineapple Waste Hydrochar in Simulated Wastewater Treatment - Thakur, Himanshi; Vikas Gupta (International Journal of Sustainable Applied Sciences, 2024)
This study explores the viability of utilizing biochar and hydrochar derived from pineapple waste as adsorbents for removing lead (Pb) from water. Pineapple residues, including stems, leaves, and fruit, were subjected to pyrolysis and Hydrothermal Treatment to produce biochar (PWB) and hydrochar (PWH) respectively. Fourier Transform Infrared (FT-IR) analysis was employed to characterize the surface properties of PWB and PWH, validating their potential as adsorbents. A series of adsorption experiments assessed the impact of pH (ranging from 2 to 6), contact time (ranging from 15 to 90 minutes), and temperature (ranging from 30 to 90°C) on the adsorption efficiency of both materials. Results indicate PWH to be markedly more effective, with an average Pb removal efficiency of 84.07% compared to PWB's 55.68%. The optimal contact time was determined to be 60 minutes for both materials. Moreover, pH 4.0 was identified as the optimal condition for Pb adsorption, showcasing a significant increase in biosorption capacity within this pH range. Additionally, higher temperatures corresponded to enhanced Pb2+ removal efficiency, rising from 75.02% to 87.58% as temperature increased from 30°C to 90°C. Overall, these findings underscore the potential of pineapple waste-derived biochar and hydrochar as promising, environmentally friendly adsorbents for addressing heavy metal contamination in water, particularly in wastewater treatment applications.